Autophagy modulates endoplasmic reticulum stress-induced cell death in podocytes: A protective role. (April 2015) - Cheng, Yu-Chi; Chang, Jer-Ming; Chen, Chien-An; Chen, Hung-Chun
Endoplasmic reticulum stress occurs in a variety of patho-physiological mechanisms and there has been great interest in managing this pathway for the treatment of clinical diseases. Autophagy is closely interconnected with endoplasmic reticulum stress to counteract the possible injurious effects related with the impairment of protein folding. Studies have shown that glomerular podocytes exhibit high rate of autophagy to maintain as terminally differentiated cells. In this study, podocytes were exposed to tunicamycin and thapsigargin to induce endoplasmic reticulum stress. Thapsigargin/tunicamycin treatment induced a significant increase in endoplasmic reticulum stress and of cell death, represented by higher GADD153 and GRP78 expression and propidium iodide flow cytometry, respectively. However, thapsigargin/tunicamycin stimulation also enhanced autophagy development, demonstrated by monodansylcadaverine assay and LC3 conversion. To evaluate the regulatory effects of autophagy on endoplasmic reticulum stress-induced cell death, rapamycin (Rap) or 3-methyladenine (3-MA) was added to enhance or inhibit autophagosome formation. Endoplasmic reticulum stress-induced cell death was decreased at 6 h, but was not reduced at 24 h after Rap+TG or Rap+TM treatment. In contrast, endoplasmic reticulum stress-induced cell death increased at 6 and 24 h after 3-MA+TG or 3-MA+TM treatment. Our study demonstrated that thapsigargin/tunicamycin treatment induced endoplasmic reticulum stress which resulted in podocytes death. Autophagy, which counteracted the induced endoplasmic reticulum stress, was simultaneously enhanced. The salvational role of autophagy was supported by adding Rap/3-MA to mechanistically regulate the expression of autophagy and autophagosome formation. In summary, autophagy helps the podocytes from cell death and may contribute to sustain the longevity as a highly differentiated cell lineage.